2015
DOI: 10.1002/anie.201504529
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of 3,4,5‐Trisubstituted Isoxazoles from Morita–Baylis–Hillman Acetates by an NaNO2/I2‐Mediated Domino Reaction

Abstract: An efficient NaNO2 /I2 -mediated one-pot transformation of Morita-Baylis-Hillman (MBH) acetates into alkyl 3-nitro-5-(aryl/alkyl)isoxazole-4-carboxylates is described. In a cascade event, initial Michael addition of NaNO2 to the MBH acetate furnishes the allylnitro intermediate which undergoes I2 -catalyzed oxidative α-CH nitration of the nitromethyl subunit followed by [3+2] cycloaddition to afford the title compounds. Structural elaborations of these highly substituted isoxazoles by SN Ar reactions and hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 56 publications
(16 reference statements)
1
21
0
Order By: Relevance
“…[18] Thereaction begins with the anodic oxidation of 3 (E p/2 = 0.52 Vv s. SCE) into the corresponding radical cation 3C + .Meanwhile,H 2 Oisreduced at the cathode to produce H 2 and HO À ,t he latter of which then deprotonates the 1,3-dicarbonyl compound I [E p/2 (2) > 2.0 Vv s. SCE] to generate the more oxidizable anion II (E p/2 = 0.31 Vv s. SCE, R = OMe). [24] Scheme 4. [24] Scheme 4.…”
mentioning
confidence: 99%
“…[18] Thereaction begins with the anodic oxidation of 3 (E p/2 = 0.52 Vv s. SCE) into the corresponding radical cation 3C + .Meanwhile,H 2 Oisreduced at the cathode to produce H 2 and HO À ,t he latter of which then deprotonates the 1,3-dicarbonyl compound I [E p/2 (2) > 2.0 Vv s. SCE] to generate the more oxidizable anion II (E p/2 = 0.31 Vv s. SCE, R = OMe). [24] Scheme 4. [24] Scheme 4.…”
mentioning
confidence: 99%
“…We have been studying the applicationso fN aNO 2 and I 2 for preparing useful products in the realmso fs ynthetic chemistry. [12] During the course of one of our studiesr elated to metalfree oxidativen itrationo fa-carbont oc arbonyl in acetophenonesw ith NaNO 2 /I 2 ,w ed iscovered that the reaction of 4'aminoacetophenone insteado fp roducing the expected product, at hiohydroximic acid, afforded4 '-iodoacetophenone in 62 %y ield. [12c] This result suggested that 4'-aminoacetophenone underwent nucleophilics ubstitution of the aminog roup with I 2 rathert han nitration of the a-carbono ft he carbonyl group.…”
mentioning
confidence: 99%
“…Our group developed a NaNO 2 /I 2 ‐mediated one‐pot transformation of MBH acetates 90 to substituted 3‐nitroisoxazoles 91 (Scheme ) . The procedure that has broad substrate scope and is scalable, proceeds via a cascade process wherein Michael addition of NO 2 – onto MBH acetate 90 affords the allylnitro derivative LXX which transforms into LXXI by liberation of a proton (Scheme ).…”
Section: Nano2‐mediated Heterocycle Formation Reactionmentioning
confidence: 99%